2017
DOI: 10.1002/mnfr.201700300
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Two Healthy Dietary Patterns Restored Microbiota Dysbiosis in Obese Patients with Metabolic Dysfunction

Abstract: Scope The consumption of two healthy diets (Mediterranean (MED) and low‐fat (LF) diets) may restore the gut microbiome dysbiosis in obese patients depending on the degree of metabolic dysfunction. Methods and results The differences in bacterial community at baseline and after 2 years of dietary intervention of 106 subjects from the CORDIOPREV study were analyzed, 33 of whom were obese patients with severe metabolic disease (5 criteria for metabolic syndrome) (MetS‐OB), 32 obese patients without metabolic dysf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
83
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(100 citation statements)
references
References 45 publications
6
83
3
1
Order By: Relevance
“…As our prescribed diet was mild, no notable effects on gut microbiota had been seen in the placebo group of this study, although previous restricted dietary interventions showed alterations in gut microbiota of obese individuals (36,37). Since the dietary recommendations were the same in both groups and no significant change in gut microbiota was observed in the placebo group, gut microbial alteration in the metformin group could be attributed to the metformin intervention.…”
Section: Discussionmentioning
confidence: 59%
“…As our prescribed diet was mild, no notable effects on gut microbiota had been seen in the placebo group of this study, although previous restricted dietary interventions showed alterations in gut microbiota of obese individuals (36,37). Since the dietary recommendations were the same in both groups and no significant change in gut microbiota was observed in the placebo group, gut microbial alteration in the metformin group could be attributed to the metformin intervention.…”
Section: Discussionmentioning
confidence: 59%
“…Dietary strategies, which presumably act by modifying the microbiome, are of great interest in preventing and treating metabolic disorders . In fact, we have previously shown that the long‐term consumption of both MED or LF diets partially restores the gut microbiota dysbiosis in obese people with the full characteristics of MetS (five criteria), whereas no significant modifications of gut microbiota were observed in NonMetS patients after the dietary intervention . Based on this, in the current work, we analyzed whether the long‐term consumption of these diets induced different microbiota changes in men than in women with MetS.…”
Section: Discussionmentioning
confidence: 93%
“…Dietary patterns that consider dietary quality and diversity may inform future habitual dietary strategies for durable microbial shifts, as opposed to a short-term transient initiative. For example, after 2 years, consumption of a Mediterranean dietary pattern and a low-fat dietary pattern has been shown to partially restore loss of keystone taxa in 33 participants with obesity and varying levels of metabolic dysfunction [101]. Regardless, contrary to most studies, habitual dietary intake should be taken into account in acute dietary interventions considering the long-lasting role dietary history has on the composition of the gut microbiota unless faced with an extreme dietary shift [102].…”
Section: Dietary Indicesmentioning
confidence: 99%